(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The role of basic quantities influencing the process of laser raster marking of AISI 304 stainless steel products using a fiber laser was investigated. Some dependencies were found when changing the contrast of the marking when changing the parameters in wide intervals. As the raster step increases, a non-linear decrease in contrast occurs as the rate of contrast decrease. Regarding the influence of the speed on the contrast, it was found that as the speed increases, the contrast of the marking decreases non-linearly, and as the step increases, the speed of the contrast decrease also increases. Above 20 kHz, the frequency has relatively little influence on the contrast, as with increasing frequency the contrast slowly increases and the dependence is almost linear. The effective energy is strongly influenced by the contrast. At effective energy values below 18 kJ/cm2 the contrast of the marking is insufficient for visual perception of a good quality marking, but in the interval from 6 kJ/cm2 to 46 kJ/cm2 the contrast increases very quickly. At values of the effective energy above 100 kJ/cm2, the contrast of the marking hardly changes. The obtained results can be used by the operators of laser systems to evaluate the working ranges and quickly determine the boundary areas of the optimal technological parameters when obtaining a good contrast in the laser marking of stainless steels with a fiber laser.